2004
DOI: 10.1016/j.jaci.2004.03.015
|View full text |Cite
|
Sign up to set email alerts
|

The role of the tachykinin NK1 receptor in airway changes in a mouse model of allergic asthma

Abstract: Background: Tachykinins are present in sensory nerves and in nonneuronal cells like macrophages. Human data suggest a role for these peptides in asthma, but the exact role of tachykinins and their receptors in allergic airway inflammation is still a matter of debate. Objective: The aim of this study was to determine the role of the tachykinin NK 1 receptor in allergic airway responses in a mouse model. Methods: Tachykinin NK 1 receptor wild-type and knockout animals were sensitized intraperitoneally to ovalbum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
7
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 45 publications
1
7
1
Order By: Relevance
“…Our results demonstrate that SPinduced ROS generation is involved in the damage and the remodelling of the bronchial epithelium in vivo, as a strong reduction of both the damage and the goblet cell hyperplasia was observed after treating the animals with SR 140333 or NAC, respectively. While an earlier study did not find a reduction of epithelial damage in NK1 knockout mice, the promotion of remodelling was shown to be related to the NK-1 receptor, as seen in goblet cell hyperplasia [40], which was also seen in our model, but the earlier study did not assess the role of ROS in this context. NK-1 inhibition resulted in decreased inflammatory cell influx to airway tissues and BAL fluid, which has also been observed in an earlier study [41].…”
Section: Discussioncontrasting
confidence: 75%
“…Our results demonstrate that SPinduced ROS generation is involved in the damage and the remodelling of the bronchial epithelium in vivo, as a strong reduction of both the damage and the goblet cell hyperplasia was observed after treating the animals with SR 140333 or NAC, respectively. While an earlier study did not find a reduction of epithelial damage in NK1 knockout mice, the promotion of remodelling was shown to be related to the NK-1 receptor, as seen in goblet cell hyperplasia [40], which was also seen in our model, but the earlier study did not assess the role of ROS in this context. NK-1 inhibition resulted in decreased inflammatory cell influx to airway tissues and BAL fluid, which has also been observed in an earlier study [41].…”
Section: Discussioncontrasting
confidence: 75%
“…When given i.p. sensitization, several investigators found that there was no difference in BHR between animals with and without sensitization [19,29,30,31], while others indicated an increased bronchial responsiveness in animals given OVA compared to vehicle [28,32,33]. As for animals sensitized with i.n.…”
Section: Discussionmentioning
confidence: 99%
“…The observed contractile response to antigen is due to activation of mast cells via antigen cross-linking of IgE antibodies bound on the high affinity IgE receptor FcεRI [24]. It is important to note that no differences in serum ovalbumin-specific IgE levels between the tachykinin NK 1 receptor WT and KO mice can be detected [25]. Upon activation, mast cells previously been demonstrated in rats [17] and in mice but this depended on the inbred strain of mice used [16;18].…”
Section: Discussionmentioning
confidence: 98%